The Use of Digital Marketing Communication Media as a Tool to Achieve Brand Awareness of Kitchenindo Products - Ahmad Vinza Riskyawan; Rizka Miladiah Ervianty (TIJAB (The International Journal of Applied Business), 2019)
There are various ways to use the internet technology for marketers. One of them is the use of social media as a means for marketers to inform or sell products or services for customers' online market share. Social media is a new marketing tool that makes it possible to know customers and prospective customers in ways that were previously impossible (Clayman, 2017). The subjects of this study were the people of Surabaya, who were selected by simple random sampling. This study uses a Likert scale as a measurement scale, which consists of four answer choices. This was used to accommodate differences in respondents' answers between categories of respondents. Data collection was carried out through a questionnaire containing several questions which were then recorded, calculated on average per dimension, and analyzed descriptively. The questionnaire in this study employed to measure the effectiveness of advertising is based on EPIC theory (Empathy, Persuation, Impact, and Communication - EPIC), and to measure brand awareness is based on the brand awareness of the pyramid theory (top of mid, brand recall, brand recognition, and unaware of the brand) by David Aaker quoted in Durianto (2004). All respondents knew the Kitchenindo brand with the help of content or advertisements through the Kitchenindo Instagram account and respondents rated Kitchenindo's ads or content on Instagram as effective. Thus, the use of digital marketing communication media can be used as a tool to achieve the awareness of the Kitchenindo brand, although this research only reached the brand recognition stage and has not reached the level of brand recall and even top of mind. This turned out to have an impact on the number of product sales figures that did not significantly give benefit to the company.